Caries management for institutionalized elders using fluoride and chlorhexidine mouthrinses - Wyatt CCL, MacEntee MI. (Blackwell Synergy, 2004)
The effectiveness of either a 0.2% neutral sodium fluoride (NaF) solution or a 0.12% chlorhexidine (CHX) solution as a daily mouthrinse for controlling caries was tested against a placebo rinse in this 2-year randomized clinical trial among elders in long-term care (LTC) facilities